Quantifying the effect of COVID-19 pandemic lockdown among the summer crop growers of Uttar Pradesh - DUBEY, S K; SINGH, ATAR; SINGH, A K; SAH, UMA; PANDEY, SADHNA; SINGH, RAGHWENDRA; SINGH, RAJEEV KUMAR; PANDEY, AMAN KUMAR (The Indian Journal of Agricultural Sciences, 2023)
Telephonic survey was done with randomly sampled 570 farmers spread across 57 districts representing eastern (16 districts), western (17 districts), central (16 districts) and Bundelkhand (7 districts) zones of Uttar Pradesh during the period of 20 April–25 June, 2020 to ascertain the effect of COVID-19 lockdown on the investment and profitability of the summer crops grown by them. Farmers’ responses were compared with their observations on the same variable during the same period of previous year, i.e. 2019. Suitable descriptive and inferential statistical treatments were given to collected data. Results established that there was maximum increase in all cost components for summer maize (8.74–16.21%) followed by okra (7.40–16.24%) and bottle gourd (7–16%). Summer greengram also had similar trends of cost increase (8–17%). Summer groundnut (3.55–5.54%) witnessed a relatively lesser increase for all costs except the plant protection cost (20.19%). Thus, compared to last year (2019), the cost components significantly increased for all the cultivated crops in summer. However, the government facilitation coupled with favourable climatic conditions helped the summer crop growers to harvest better yield advantage (4–10%) and accordingly the enhanced market price (5.02–8.52% more) increased profitability index (1.02–14.44%). The parameters like per unit production and plant protection cost emerged as the most prominent determinants of the net return of most of the summer crops during COVID-19 lockdown.